Absolute diode laser-based in situ detection of HCl in gasification processes - Ortwein, Pascal; Woiwode, W.; Fleck, S.; Eberhard, M.; Kolb, T.; Wagner, Steven; Gisi, M.; Ebert, Volker (Experiments in fluids, 2010)
The release of HCl is an important parameter for industrial combustion and gasification processes, which must be determined in the ppm range for active process control and optimization. Based on a low power vertical-cavity surface-emitting laser (VCSEL) at 1.74 μm, we developed a new tuneable diode laser absorption spectrometer for calibration-free, absolute in situ HCl detection using the H35Cl (2 ← 0) R(3) absorption line with minimized cross-sensitivity to CO2 and H2O. The spectrometer was applied to in situ measurements in a gasification process (T = 1,130°C, P = 1 atm, L = 28 cm) and yielded an optical resolution of 2.3·10−4, i.e. a HCl sensitivity of 45 ppm (13 ppm·m).
Gesehen am 16.06.2023